2009
DOI: 10.21273/jashs.134.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidizing Enzyme Activities in Chilling-sensitive and Chilling-tolerant Pepper Fruit as Affected by Stage of Ripeness and Storage Temperature

Abstract: To study ripening-related chilling injury in pepper (Capsicum annuum L.), chilling-tolerant ‘Buchon’ and chilling-sensitive ‘Nockgwang’ fruit were harvested at mature green (MG), breaker (BR), and red-ripe (RR) stages and stored at 1, 5, and 10 °C for 21 d. ‘Buchon’ did not show surface pitting (SP) regardless of ripeness stage and storage temperature, whereas ‘Nockgwang’ at MG and BR exhibited SP at 1 and 5 °C. After 14 days of storage at 1 °C, chilling-sensitive ‘Nockgwang’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…During CI loss of redox homeostasis because of a disproportionate increase in ROS production, causing oxidative stress is a distinctive effect of low temperatures in plant organs [4]. Changes in MDA production, which reflect the rise of lipid peroxidation of cell membranes caused by ROS accumulation [29], were also observed in chilled fruits (Table 1). It is interesting to point out that the MDA increase in chilled fruits is associated to plastid degradation and the disappearance of peroxisomes in chilled fruits (Figure 1, L, O), the decrease in the activities of antioxidant enzymes (CAT and POX) (supplementary table S1), and the data obtained from the proteomic study (Table 2) in which "redox metabolism" is one of the two major functional classes affected by cold stress.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…During CI loss of redox homeostasis because of a disproportionate increase in ROS production, causing oxidative stress is a distinctive effect of low temperatures in plant organs [4]. Changes in MDA production, which reflect the rise of lipid peroxidation of cell membranes caused by ROS accumulation [29], were also observed in chilled fruits (Table 1). It is interesting to point out that the MDA increase in chilled fruits is associated to plastid degradation and the disappearance of peroxisomes in chilled fruits (Figure 1, L, O), the decrease in the activities of antioxidant enzymes (CAT and POX) (supplementary table S1), and the data obtained from the proteomic study (Table 2) in which "redox metabolism" is one of the two major functional classes affected by cold stress.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, an increase in ethylene production was observed in chilled fruits (Table 1). In many cold-sensitive plant systems, low temperatures stimulate ethylene biosynthesis together with development of CI, and these events have been associated with an increase in the contents of precursors of ethylene biosynthesis or in the activities of enzymes involved in the biosynthetic pathway [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, our results indicate that the increased enzyme activity triggered by urea could confer increased protection during storage at low temperatures as, compared with the control, lower activity of defensive enzymes at chilling temperatures can impair the plant's ability to break products of oxygen photoreduction 51. Additionally, Lim et al 53 found that chilling increases the level of active oxygen species (AOS) in chilling‐sensitive plants and reduction of the chilling in resistant plants may be related to their ability to reduce and/or scavenge free radicals through increased enzyme activity. Thus lower activities of CAT were observed in chilling‐sensitive fruit than in tolerant fruit after storage at 0 °C 54.…”
Section: Resultsmentioning
confidence: 99%
“…The successive cellular events that occur in chilling conditions have often been investigated in different species under controlled conditions (Lim et al 2009;Bonnecarrere et al 2011). The main studies have been conducted on deciduous species in which cold treatments were applied abruptly in a growth chamber, with no transition period and under conditions of constant growth.…”
Section: Discussionmentioning
confidence: 99%